OCCURRENCE OF LISTERIA SPECIES IN SOME FOOD ITEMS SOLD IN PARTS OF KADUNA, NIGERIA - Hammuel, C.; Abdullahi, I. O.; Whong, C. M. Z.; Kadima, K. B. (FUDMA JOURNAL OF SCIENCES, 2023)
Listeriosis is a disease of humans and animals cause by pathogenic Listeria species and are associated with various types of food items of both animals and plants origin. The aim of this work was to assess the occurrence of Listeria species in some foods items sold from four selected markets in two Local Government Areas of Kaduna State. A total number of 400 samples were collected, 100 samples each from the four locations comprising 25 sample each of beef, chicken, lettuce and cabbage were collected from Samaru, Sabon Gari, Kakuri and Ungwan Boro markets. These samples were analysed for Listeria species using Listeria selective media and biochemical tests. The isolates of the Listeria species were further confirmed using microgen listeria identification system. The overall prevalence of Listeria species in the selected food samples in the four locations was 9.8%. Listeria species were isolated from beef (6.0%), Chicken (15.0%), cabbage (6.0%) and lettuce (12.0%). Listeria ivanovii (8.0%) was detected in the food samples; other species include Listeria grayi (1.5%) and Listeria welshimeri (0.25%). Therefore, the presence of Listeria species in the selected food samples suggests that the foods might be important source of listeriosis.